La evolución de las tecnologías de información deportiva. - Wilson, Wayne (Revista General de Información y Documentación, 2000)
The article analyses the development of sports documentation promoted by information technologies, the use of databases, CD-Rs and the Internet, as well as the role that should be played by sports librarians and documentalists with regard to these technologies
Keywords: Sports documentation; Information technologies; Databases; CD-R; Internet